Electrophysiological insights into conceptual disorganization in schizophrenia - Kiang, Michael (2007)
Disorganized speech, or thought disorder, in schizophrenia may reflect abnormal processing of meaningful concepts. To examine whether schizophrenia involves abnormalities in how a meaningful context influences processing of concepts strongly, weakly, or not related to it, we used the N400, an event-related brain potential (ERP) index of semantic relatedness. ERPs were recorded from schizophrenia patients (n=18) and normal controls (n=18) while they viewed category definitions (e.g., a type of fruit), each followed by a target word that was either a high-typicality category exemplar (apple), low-typicality exemplar (cherry), or non-exemplar (clamp). Participants' task was to indicate via button-press whether or not the target belonged to the category. In both patients and controls, N400 amplitude was largest (most negative) for non-exemplars, intermediate for low-typicality exemplars, and smallest (least negative) for high-typicality exemplars. Compared to controls, patients showed a trend toward reduced N400 amplitude differences between non-exemplars and low-typicality exemplars. Most importantly, within patients, reduced N400 amplitude differences between high- and low-typicality exemplars were correlated with psychotic symptoms. In schizophrenia patients, an N400 index of semantic processing was associated with psychotic symptoms. Psychosis may be associated with greater similarity in how concepts strongly and weakly meaningfully related to their context are processed.